Dressed in Nature: Women and Text/Styles in Painting and Literature, from Renaissance Aesthetics to Pre-Raphaelite Poetics and to Art Nouveau Painting - Carmen Concilio; Costanza Mondo (ZoneModa Journal, 2025)
This contribution focuses on paintings and poetry, visualizing fashionable design in clothing, such as flowers, foliage and greenery — characterizing pre-Raphaelite poetry and painting. This paper analyses Sandro Botticelli’s Spring (1477–82) and its representation of clothing, flowers and natural patterns which take on transformative, symbolical and connotative traits especially in Chloris’ metamorphosis. John Everett Millais’ Ophelia (1851–2) is then framed through Shakespeare’s Hamlet and Rossetti’s poem The Portrait (1870). The nature-steeped poem The Lady of Shalott — which inspired the singer Loreena McKennit — is then made to address the photograph The Lady of Shalott by the contemporary American-German photographer Julia Fullerton-Batten, who recreates John William Waterhouse’s painting emphasizing the textile dimension and the symbolic power of greenery. This dialogue between painting and poetry foregrounds the description of garments and textiles, their connection with the natural world, and human vs nonhuman kinship which offers symbolical, allegorical and pictorial readings of artworks and poems. In conclusion, the critical analysis moves on to Gustav Klimt’s painting The Kiss (1907–1908), example of art nouveau epitomizing this diachronic comparatist discourse and showing the culmination of all the elements discussed. This paper employs the frameworks of art history criticism, literary theory and environmental humanities.